PENGARUH CORPORATE GOVERNANCE, GROWTH OPPORTUNITY, PROFITABILITAS DAN LEVERAGE TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2020-2022 - Veni Eka Rismawati; Ida Nurhayati (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2023)
The main objective of this study is to examine the effect of managerial ownership, institutional ownership, growth opportunities, profitability and leverage on accounting conservatism. a score of 528 limited observations of the Manufacturing Industry listed on the Indonesia Stock Exchange for the 2020-2022 period. The research approach uses quantitative data with a purposive sampling method to determine the sample and 239 samples are taken. The results of multiple linear regression tests, namely managerial ownership, institutional ownership, growth opportunities have no impact on accounting conservatism, according to the findings of the analysis, while profitability has a negative impact and leverage has a positive impact.